Reconstructing the Gerdrup Grave – : the story of an unusual Viking Age double grave in context and in the light of new analysis - Kastholm, Ole; Margaryan, Ashot (Danish Journal of Archaeology, 2021)
In 1981, a double burial from the 9th century was excavated at Gerdrup north of Roskilde. In the grave was a woman and a man. The woman was buried with a spear, while the man had apparently been killed before the burial. The tomb has been perceived as a ‘Master and Slave burial’, which was placed on a desolate site, perhaps because the buried were seen as pariahs. However, hitherto unpublished excavation data combined with new 14C analyzes show that the burial was part of a small multi-period burial site placed near a group of older burial mounds. Topographic analyses indicate that the burial was also located at a central ford, and thus had a prominent location. Not least, new DNA analyzes surprisingly show that the two buried have a parent-offspring relation; they are mother and son. The previous perception of the Gerdrup grave is thus challenged. This article intends to present the relevant excavation data and to discuss it in the light of the new analyzes.